A liquid crystal-based sensitive element for optical sensors of cholesterol - Vistak, M.V.; Dmytrakh, V.E.; Mykytyuk, Z.M.; Petryshak, V.S.; Horbenko, Y.Y. (Functional Materials, 2017)
Composites based on cholesteric-nematic mixtures of nematic 5CB and cholesteric BLO-61 are proposed as active materials for cholesterol optical sensor.